Sorafenib Inhibits Tumor Growth and Improves Survival in a Transgenic Mouse Model of Pancreatic Islet Cell Tumors - Volker Fendrich; Katja Maschuw; Johannes Rehm; Malte Buchholz; Julia P. Holler; Emily P. Slater; Detlef K. Bartsch; Jens Waldmann (The Scientific World Journal)
Background. The purpose of the study was to evaluate Sorafenib (BAY 43-9006) derived receptor tyrosine kinase inhibition on tumor progression in murine islet cell tumors. Sorafenib is considered to be a potent inhibitor of tumor angiogenesis and neovascularization in various solid tumors. Rip1Tag2 mice were treated in two different groups according to the model of tumor progression: the early treatment group received vehicle or Sorafenib from 10 to 14 weeks of age and the late treatment group from week 12 until death. Tumor surface, tumor cell proliferation, and apoptosis were measured in both treatment groups to assess the in vivo effects of Sorafenib. Survival was recorded for the late treatment group. In the early treatment group Sorafenib led to a dramatic decrease in tumor volume compared to the control group. Apoptosis was significantly augmented and cell proliferation was inhibited. As a single therapy Sorafenib significantly improved survival in the late treatment group. Conclusion. Sorafenib may provide a new paradigm for the therapy of islet cell tumors.